Educational Game Development for Middle School Students' English Vocabulary Learning - Made Dona Wahyu; Ni Made Lisma Martarini; I Gede Made Yudi Antara; Ni Kadek Damayanti (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2026)
Student interest and participation in learning will influence learning success. Because the higher the student's interest, the better their ability and understanding of the subjects being studied. English learning at the junior high school level still faces various obstacles, one of which is low vocabulary skills or vocabulary in English. Vocabulary serves as the basis for communication and contributes to language skills. The application of technology-based learning media such as educational games can be used to improve the quality of the teaching and learning process in schools. This study aims to develop an Android educational game as a medium for learning English vocabulary. The development of this educational game uses the Game Development Life Cycle (GDLC) method.The results of the Black Box test show that all the main functions of the application, starting from the process of opening the application, menu navigation, character and camera control, mission completion mechanism, game time management, to the function of repeating the game and exiting the application, have run according to the designed specifications.